Blab! volume 1 ebook - Beauchamp, Monte (Blab!, 2023)
BLAB!—the Harvey Award-winning anthology of cutting-edge comics, art, and culture—has returned to its comics roots with a stellar lineup of contributors.Noah Van Sciver depicts the tragic demise of Crime Does Not Pay editor Robert Wood. Ryan Heshka recounts the rise and fall of Superman creators Siegel and Shuster. Sasha Velour portrays the making of film director F.W. Murnau's Nosferatu. Children's book illustrator Giselle Potter examines Peter Rabbit author Beatrix Potter's passion as a naturalist. Illustrated articles include the history of the gorilla and a report on UFOs.All this and much more in Comics and Stories That Will Make You BLAB!